Pick and place programmable logic controller system for hot press forming - Tan, Yee Siang (2017)
The main purpose of this project is to improve transfer duration time during the hot press forming. Before that, a clear study on hot press forming process has been conducted. This project motivated by using Programmable Logic Controller (PLC) to control a transfer unit machine to pick and place the blank from the furnace to stamping tool during the hot press forming. PLC was used because it offers easy installation and alteration compare to other control system such as relays and computer control, at the same time PLC also can be reused by other system easily by creating new ladder diagram and downloads it to the current PLC. For this project, a transfer unit machine fabricated and improved by different designs of transfer unit which are first design, second design and third design. Besides that, 3 methods of transfer process compared which are traditional method, 90° transfer path and 180° transfer path to improve the transfer duration time. After the ladder diagram for each method designed and compiled to PLC, PLC will generate the system. Stimulation and testing conducted to ensure the process and program are correct. Experimental then conducted and correct the result. The result shows that the third design of the transfer unit has the shortest transfer duration time and the highest percentage improvement if compared to other method and design of transfer unit. In conclusion, third design improve the transfer duration time with 28.5% improvement and it is low cost installation and high efficiency of transfer unit machine.